2002
DOI: 10.1007/s11661-002-0059-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of composition and austenite deformation on the transformation characteristics of low-carbon and ultralow-carbon microalloyed steels

Abstract: Deformation dilatometry has been used to simulate controlled hot rolling followed by controlled cooling of a group of low-and ultralow-carbon microalloyed steels containing additions of boron and/or molybdenum to enhance hardenability. Each alloy was subjected to simulated recrystallization and nonrecrystallization rolling schedules, followed by controlled cooling at rates from 0.1 ЊC/s to about 100 ЊC/s, and the corresponding continuous-cooling-transformation (CCT) diagrams were constructed. The resultant mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 32 publications
2
47
0
Order By: Relevance
“…(9) and (10) are compared to experimental values. In this case the hardness values reported by Cizek et al 13) for a Nb microalloyed steel (steel A, 0.046%C-0.212%Si-1.64%Mn-0.045%Mo-0.029%Nb-0.015%Ti) and a Nb-Mo microalloyed steel (steel B, 0.043%C-0.21%Si-1.67%Mn-0.26%Mo-0.022%Nb-0.016%Ti) are also included in the figure in terms of model validation. These steels were submitted to two thermomechanical cycles designed to produce different austenite conditions: non-deformed austenite and deformed austenite.…”
Section: Transformation Start and Finish Temperaturesmentioning
confidence: 67%
See 1 more Smart Citation
“…(9) and (10) are compared to experimental values. In this case the hardness values reported by Cizek et al 13) for a Nb microalloyed steel (steel A, 0.046%C-0.212%Si-1.64%Mn-0.045%Mo-0.029%Nb-0.015%Ti) and a Nb-Mo microalloyed steel (steel B, 0.043%C-0.21%Si-1.67%Mn-0.26%Mo-0.022%Nb-0.016%Ti) are also included in the figure in terms of model validation. These steels were submitted to two thermomechanical cycles designed to produce different austenite conditions: non-deformed austenite and deformed austenite.…”
Section: Transformation Start and Finish Temperaturesmentioning
confidence: 67%
“…On one hand, it seems reasonable that the terms %C, %Mn, %Nb and %Mo contain a negative sign, denoting the retardation effect on the transformation associated with these elements in solid solution. Cizek et al 13) found that microalloying elements cause a decrease in transformation start temperature. Nb and Mo tend to segregate at the austenite boundaries and deformation-induced boundaries.…”
Section: Transformation Start and Finish Temperaturesmentioning
confidence: 99%
“…6, showing microstructure consisting of granular bainite (GB), upper bainite (UB) and lath bainite (LB) distinguished based on bainite features. 21,22) The granular bainite (denoted by white arrow in Fig. 6(a)) consists of lath ferrite with low misorientations, containing equiaxed M/A constituents, but these lath boundaries can not be observed in OM pictures.…”
Section: Microstructural Characteristics Of Tested Steel Processed Bymentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12] These studies mainly focus on effect of chemical compositions, austenite state (undeformed or recrystallized austenite and deformed austenite) or cooling rate on phase transformation behaviors, however, systematic work on influence of deformation temperature on Ar3 temperature and quantitative relationship between Ar3 temperature, deformation temperature and cooling rates is lack. Bengochea et al 4) and Eghbali et al 5) mainly indicated influence of deformation temperature and prior austenite microstructure on ferrite grain refinement, respectively.…”
Section: Introductionmentioning
confidence: 99%